(untitled) (LACCEI, 2024)
Abstract: There is increasing attention towards materials that are environmental-friendly, low-cost, and accessible. Natural polymers such as cellulose are used as substitutes for petroleum-based polymers. Cellulose is the main constituent of all-natural fibers and is porous, inexpensive, and hydrophilic. Cellulose is also suitable for converting petroleum-based polymers into more eco-friendly materials. Several fields, such as aerospace, the automotive industry, and the military, have taken advantage of cellulose-based materials. One field where cellulose-based materials have proved their value is water treatment. Two approaches to boosting the cellulose’s potential use in membrane applications for water treatment are the synthesis of cellulose-based composites and graft copolymerization of cellulose. Both approaches have successfully enhanced cellulose’s mechanical properties. This paper mayor contributions are a) The calculation of mechanical properties from the graphs to be used as a source of information for simulations. b) The summary of the methods and tests results to decide what sources of cellulose are available to emulate the trials and enhance polymers properties for different applications such as membranes for water. Keywords: Cellulose, Polymer composites, Graft Copolymers. Membranes.